Repeated-doses and reproductive toxicity studies of the monoterpene 1, 8-cineole (eucalyptol) in Wistar rats. (November 2016) - Caldas, Germana Freire Rocha; Limeira, Mayara Marília Ferreira; Araújo, Alice Valença; Albuquerque, Giwellington Silva; Silva-Neto, Jacinto da Costa; Silva, Teresinha Gonçalves da; Costa-Silva, João Henrique; Menezes, Irwin Rose Alencar de; Costa, José Galberto Martins da; Wanderley, Almir Gonçalves
Abstract: 1, 8-cineole (eucalyptol) is widely used as an excipient in the pharmaceutical industry and as a food flavoring agent, thus providing significant potential for human exposure to the compound. We investigated the preclinical toxicity and reproductive toxicity of 1, 8-cineole (CIN). In the repeated-doses toxicity study for 50 days, CIN (100, 500 or 1000 mg/kg) did not produce any signs of toxicity or deaths, but affected body weight gain during the first week of treatment. The hematological and biochemical profiles did not show significant differences except for increase in the MCV, platelet and urea levels or reduction in MCHC, MPV and alkaline phosphatase. Histopathological analysis showed weak changes in the lungs, liver, kidneys and uterus. In the reproductive toxicity, CIN (250, 500 or 1000 mg/kg) produced a reduction in body weight in pregnant rats treated during the pre-implantation or organogenesis periods. The highest doses induced a reduction in the mass of fetuses (pre-implantation) and dead fetuses (both periods) of pregnant rats. The results indicate that the treatment by repeated-doses showed occasional alterations in rats of both sexes. However, provide evidence that possibly 1, 8-cineole presents maternal and fetal toxicity. This requires more detailed investigation to better characterize the toxic effects of this compound. Graphical abstract: Highlights: Cineole was tolerated well by mice up to a dose of 1500 mg/kg by oral route. The treatment (50 days) with cineole did not produce signs of toxicity or deaths. Cineole induced occasional alterations in hematological and biochemical parameters. Cineole induced histological alterations in the lungs, liver, kidneys and uterus. Cineole presents maternal and fetal toxicity in pre-implantation or organogenesis.